Satisfaction with primary care and mental health care among individuals with severe mental illness in a rural area: a seven-year follow-up study of a clinical cohort. Issue 1 (December 2016) - Ruud, Torleif; Aarre, Trond; Boeskov, Berit; Husevåg, Per; Klepp, Rigmor; Kristiansen, Synnøve; Sandvik, Jorunn
Abstract Background Most studies of services for people with severe mental illness have been performed in cities. Our 7-year follow-up study aimed to investigate clinical course and satisfaction with services among individuals with severe mental illness who received community mental health services in a rural area. The services were provided by primary care and a community mental health center (CMHC), which worked in close collaboration and emphasized individually tailored case management, relationship-building and continuity of care. Methods All 57 patients with severe mental illness who were seen by the CMHC in 1992–1993 and were still alive in 1999 were asked to participate. Retrospective ratings were performed for the first month of contact in 1992–1993 based on patient records and detailed notes. A semi-structured interview was conducted in 1999–2000 with the 40 patients (70.2 %) who gave written consent to participate in the study. DSM-IV diagnoses were made using OPCRIT. The retrospective baseline ratings and the follow-up interview included assessments of symptoms and functioning using the following instruments: the Brief Psychiatric Rating Scale Expanded version 4 (BPRS-E), the Health of the Nation Outcome Scales (HoNOS), the Global Assessment of Functioning Scale (split version), and the Practical and Social Functioning Scale (PSF). Results The ratings revealed improvements in psychiatric problems and functioning. Patients with schizophrenia spectrum disorders improved primarily in psychotic symptoms, while patients with severe affective disorders improved primarily in affective symptoms. Large variations in the use of primary care and mental health services were observed, with more intensive specialized mental health services for individuals with schizophrenia spectrum disorders than severe affective disorders. Overall, the patients were satisfied with the provided services. They were most satisfied with GPs and more satisfied with local outpatient and inpatient services than with hospital inpatient services and medication. Conclusions Patients with severe mental illness in a rural area value local services that emphasize relationships and close collaborations among the CMHC, GPs and primary health and social care. Even in an area with a fairly well-staffed CMHC, the highest patient satisfaction was reported for GPs, indicating the potential key role of GPs for this patient group.